Drillability apparatus at the Agricultural Engineering Laboratory (1953)
General view of an unidentified room at the U.S. Department of Agriculture's Agricultural Engineering Laboratory showing a drillability apparatus with fertilizer hoppers, a starwheel, and rotating plate mechanism.
Keywords: Nitrogen fertilizer industry; United States. Bureau of Chemistry and Soils; Fertilizer industry--Equipment and supplies; United States. Department of Agriculture; Machinery